2014
DOI: 10.1007/s13277-014-2853-5
|View full text |Cite
|
Sign up to set email alerts
|

Individualized chemotherapy for osteosarcoma and identification of gene mutations in osteosarcoma

Abstract: The study aims to identify novel gene mutations in osteosarcoma and to guide individualized preoperative chemotherapy for osteosarcoma based on the analysis of expression and mutations of the drug-metabolism-related genes. Twenty-eight osteosarcoma patients received individualized preoperative chemotherapy regimens. Expression levels and mutations of chemotherapy-related genes in samples collected from the patients were determined using real-time PCR and DNA sequencing, respectively. Patient sensitivity to che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Because MFOS has a much worse prognosis than single lesion OS, a bone scan is indicated on the first hospital visit of a patient with an OS to determine whether there are multiple tumors. Use of chemotherapy drugs to which the tumor is sensitive according to sequencing may enable more effective chemotherapy, as has been shown for adolescent patients with single lesion OS. Patients with MFOS, whose tumors are more likely to be drug‐resistant, may benefit from drug sensitive detection, which could avert progression and prolong overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because MFOS has a much worse prognosis than single lesion OS, a bone scan is indicated on the first hospital visit of a patient with an OS to determine whether there are multiple tumors. Use of chemotherapy drugs to which the tumor is sensitive according to sequencing may enable more effective chemotherapy, as has been shown for adolescent patients with single lesion OS. Patients with MFOS, whose tumors are more likely to be drug‐resistant, may benefit from drug sensitive detection, which could avert progression and prolong overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, vemurafenib, a mutation‐specific BRAF inhibitor, has successfully been used to treat metastatic melanoma. With the rapid progress in gene sequencing and application of precision medicine, oncogene like HER2, c‐myc, c‐fos, MDM2, SAS, anti‐oncogenes such as TP53, Rb, p16 (expressed gene mutations of which have been implicated in the initiation and progression of metastases), CD44, matrix metalloproteinases and nm23 have also been found to be associated with the lung metastases of OS. With the help of whole gene sequencing to test tumor tissue of children and adolescent OS patients, Chen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RD represents chemotherapy sensitivity, while SD and PD represent drug resistance. Based on this criteria [41] RT-PCR experiments were preformed on the 68 samples to validate the mRNA expression of the identi ed differentiately expressed genes (TIMP2 and BAX). Total RNA was extracted using TRIzol reagent with manufacturer's instruction (ThermoFisher Inc., USA).…”
Section: Osteosarcoma Tissue Analysismentioning
confidence: 99%
“…The apoptotic activity by Mdm2 inhibitors mainly relies on p53 activation and the upregulation of a classic pro-apoptotic p53-target genes Puma ( Supplementary Figure 2(a) and (b)). 4,5 We next investigated whether Oridonin had impact on p53 activation. Western blotting and qRT-PCR assays showed that Oridonin had no influence on the levels of Mdm2, p53, and Puma expression and also did not affect the ability of Nutlin-3 in inducing Mdm2 and p53 accumulation and Puma upregulation in OS cell lines ( Figure 5(a)-(d)).…”
Section: Oridonin Has No Impact On Levels Of Mdm2 and P53 In Os Cellsmentioning
confidence: 99%